Hope and the joy of living, in Pieper’s philosophy - Lasala, Teresa (Dia-noesis: A Journal of Philosophy, 2024)
We live in a practical society, where work is a god to be worshipped. The almost totalitarian situation implies that most people live to work and even the spare time we dispose of is destined to rest, in order to continue with our productive life, not to live a meaningful one. The result is that there is no time to devote to personal enrichment. When the most of time and efforts are destined to work, there is nothing left to culture, arts, meditation, and philosophy. And these are the activities that precisely are to lead us to feel the joy of life. When there is nothing more than work to define who we are and what being alive means, then appears boredom and fatigue, because we miss something important. Life loses the taste of the new and its sense. Josef Pieper thinks that hope is the best attitude to walk the way of life. Hope teaches us that, in the end, it’s all right. Not a fairy tale, but a good life to live. The alternatives are certainly dreadful. One of them is a flattery optimism, condemned to frustration, and the other is hell, where desperation dwells, as Dante told us. Pieper was a Christian philosopher but lately the topic has been studied from other points of view. The power of hope shows itself in its capacity to change reality, to change our mind, first. And to change society. The real question is what we are living for. The answer could be to become the best version of ourselves and to leave a better world behind us. We can achieve this goal if we are hopeful and confident people. No matter how difficult the way may be, when there is a will, there is a way. So, let’s go and enjoy the walk. Whatever may happen, it pays the bill.